Penerapan Model Nurs Dalam Pembelajaran Membaca Bahasa Jerman - Sri Wahdaniyah; Nurming Saleh; Misnah Mannahali (Universitas Negeri Makassar, 2021)
Abstract. This research was a class action research consisting of two cycles and was conducted online. The aim of this research was to know the planning, process and outcome of the NURS model in the German reading lesson for students in class XI IPS at the SMA Negeri 2 Bantaeng. The research data were qualitative and quantitative. The qualitative data were collected by the observations and the quantitative data by the test results in the first and second cycle and analyzed by percentage technique. The result of this research showed that the average student reading comprehension score was 8 in the first cycle and 8,5 in the second cycle. This meant that the use of the NURS model in German reading lesson for students in class XI IPS at the SMA Negeri 2 Bantaeng could increase.